Antimicrobial Activity of Grape Seed Extracts on Some Species of Bacteria that Cause Urinary Tract Infection - IBRAHIM, SUAAD KHALIL (Journal of Science in Medicine and Life, 2024)
The study included the collection of (50) samples of diuresis from patients suffering from Urinary tract infection (UTI) in Al-Kindi Teaching Hospital in Baghdad and used sterile bottles for sample collection and cultured immediately after taking the sample for diagnosis. Bacterial isolates were diagnosed by performing cultured and biochemical tests and the results showed that Escherichia coli is the most common species in (UTI)patients and by (15) 47% isolation of the total 32 isolates, about (10) 31.5% from K. pneumonia, and (7) 21.5% isolates of P.aerugenosa. The sensitivity of the bacteria to (5) antibiotics (Amikacin, Ciprofloxacin, Erythromycin, Vancomycin and Gentamycin) were investigated and among different groups, all of which are sensitive to Amikacin and Ciprofloxacin, all of which are resistant to Erythromycin, E.coli and K. pneumonia, sensitive to Vancomycin, Gentamycin while P. aerugenosa resistant to them. The inhibitory effect of aqueous and alcoholic extracts of grape seed was studied for four concentrations (25), (50), (100), (200) mg/ml, for the studed bacteria. The extracts showed inhibitory effectiveness and varying effects depending on the type, concentrations of extract, and the type of microorganism. the inhibitory capacity and the effectiveness ratio of aqueous extracts was weak compared to alcoholic extracts.